Development and validation of evaluation indicators for the quality of professional life of Chinese homeroom teachers - Sun, Li; Li, Ao; Li, ShuQin; Liu, QingXiu; Lu, JingPing (Frontiers in Psychology, 2025)
IntroductionThis study aimed to develop and validate three-level evaluation indicators for the quality of professional life of homeroom teachers.MethodsThis study adopted an exploratory sequential mixed-methods design. First, we conducted semi-structured interviews with 143 homeroom teachers in China and analyzed 120 excerpts from published literature using NVivo 10. Next, 72 experts (elementary and secondary school principals) assessed and compared the evaluation indicators. We conducted statistical analysis using the Gray Statistical Method and AHP (Analytic Hierarchy Process) Calculation Method. Finally, we surveyed 661 teachers, 730 principals, and 792 teachers from Taiwan and verified the validity of the evaluation indicators using quantitative analysis methods.ResultsIn the AHP Calculation Method, when the order of the judgment matrix is greater than 2 and the CR (Consistnency Ratio) is far less than 0.1, the matrix is consistent, and weights can be further calculated. The survey results indicated that the overall occupational quality of life of head teachers was moderately low, with a score of 2.81(3 is the median for each question.), and the occupational quality of life of the sample was significantly lower than the median (3 is the median for each question.). The data obtained from the homogeneity reliability (Cronbach’s alpha) test of the questionnaire were 0.79, indicating good reliability. However, the homogeneity reliability of the Taiwan sample was unsatisfactory.ConclusionBy constructing and validating an evaluation indicator system for Chinese homeroom teachers’ professional life quality, this study provides standardized tools and empirical evidence to diagnose their professional predicaments, optimize school management, inform educational policy formulation, and advance relevant research—while introducing a scientifically weighted, employee-centered index with theoretical and practical policy significance for allowance systems and professional development programs.